possible association of HLA class-1 molecules with rheumatoid arthritis in Iraqi patients - Al-Haidary, batool A.; Al-Haidary, Khalida; Al-Khafaji, Jassim; Al-Ezzy, Mustafa; Al-Nnema, Amera (Journal of the Faculty of Medicine Baghdad, 2005)
Background: